2010
DOI: 10.1111/j.1467-7687.2010.00983.x
|View full text |Cite
|
Sign up to set email alerts
|

Rapid processing of letters, digits and symbols: what purely visual‐attentional deficit in developmental dyslexia?

Abstract: Visual-attentional theories of dyslexia predict deficits for dyslexic children not only for the perception of letter strings but also for non-alphanumeric symbol strings. This prediction was tested in a two-alternative forced-choice paradigm with letters, digits, and symbols. Children with dyslexia showed significant deficits for letter and digit strings but not for symbol strings. This finding is difficult to explain for visual-attentional theories of dyslexia which postulate identical deficits for letters, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
173
3
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(196 citation statements)
references
References 41 publications
16
173
3
4
Order By: Relevance
“…A difference between previous studies and the present one is that multi-character processing was assessed using letter sounds in this study, and not letter names. It has been suggested that a deficit in performance in letter report tasks may not be the result of reduced visual attention span, but is rather due to impaired visual to phonological mapping (Hawelka & Wimmer, 2008;Ziegler et al, 2010), in line with the phonological deficit theory of dyslexia. The letter report task undoubtedly does involve the activation of phonological information, and phonological processing should be in evidence even more when the task involves letter sounds rather than names, however, the interpretation of performance in the task has been that it allows us to assess the ability to process multiple elements in parallel.…”
Section: Discussionmentioning
confidence: 92%
“…A difference between previous studies and the present one is that multi-character processing was assessed using letter sounds in this study, and not letter names. It has been suggested that a deficit in performance in letter report tasks may not be the result of reduced visual attention span, but is rather due to impaired visual to phonological mapping (Hawelka & Wimmer, 2008;Ziegler et al, 2010), in line with the phonological deficit theory of dyslexia. The letter report task undoubtedly does involve the activation of phonological information, and phonological processing should be in evidence even more when the task involves letter sounds rather than names, however, the interpretation of performance in the task has been that it allows us to assess the ability to process multiple elements in parallel.…”
Section: Discussionmentioning
confidence: 92%
“…First, the RAN-reading association may derive from visual processes like visual pattern recognition and visual discrimination (Araújo et al, 2011;Klein, 2002;Stainthorp, Stuart, Powell, Quinlan, & Garwood, 2010). However, these explanations have not been either widely studied or supported (Di Filippo et al, 2006; Gasperini, Brizzolara, Chritofani, Casalini, & Chilosi, 2014), while the results of deficits in visualattentional processes as a cause of poor reading skill are contradictory (Ger-17 mano, Reilhac, Capellini, & Valdois, 2014;Ziegler, Pech-Georgel, Dufau, & Grainger, 2010). Second, the ability to learn arbitrary sound-symbol associations is involved in both RAN and reading (Manis et al, 1999;Ziegler, Pech-Georgel et al, 2010).…”
Section: In a Search Of Explanations For The Ran-reading Relationshipmentioning
confidence: 99%
“…However, these explanations have not been either widely studied or supported (Di Filippo et al, 2006; Gasperini, Brizzolara, Chritofani, Casalini, & Chilosi, 2014), while the results of deficits in visualattentional processes as a cause of poor reading skill are contradictory (Ger-17 mano, Reilhac, Capellini, & Valdois, 2014;Ziegler, Pech-Georgel, Dufau, & Grainger, 2010). Second, the ability to learn arbitrary sound-symbol associations is involved in both RAN and reading (Manis et al, 1999;Ziegler, Pech-Georgel et al, 2010). Third, both skills require serial processing, a notion that is supported by results showing that continuous RAN is more strongly associated with reading than discrete naming (Badian, 1993; Bowers & Swanson, 1991; Chiappe, Stringer, Siegel, & Stanovich, 2002; de Jong, 2011; Georgiou, Parrila, Cui, & Papadopoulos, 2013;Zoccolotti et al, 2013).…”
mentioning
confidence: 99%
“…It has however been argued that poor performance in letter report tasks might be due to verbal deficits in encoding and reporting letters, and as such reflected a visual-tophonology code mapping disorder (Ziegler, Pech-Georgel, Dufau, & Grainger, 2010) rather than a visual attention resource limitation. Ziegler et al (2010)'s account is based on data from a forced choice detection task in which children were shown briefly presented strings of letters, digits or symbols. At the offset of the multi-character string, participants had to choose which one of two characters previously occurred in a cued position within the string.…”
Section: The Visual Attention Span Deficit Hypothesis: Developmental mentioning
confidence: 99%